Sanksi Pidana Bagi Kegiatan Mereview Suatu Produk Usaha di Media Sosial Tanpa Izin - Bagus Andika Artha Surya; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2021)
In the competitive world of business, one effective way as a means of promotion is reviewing or reviewing products, which are activities carried out by consumers to give their impressions and views about a product so that it becomes a consideration for other consumers before buying the product, but there are negative impacts from this activity, namely if it is misused by irresponsible persons, what happens is that the person gives a bad image to business actors because of these activities and affects consumers who will buy the product. The purpose of this study is to analyze the sanctions that can be imposed from reviewing or reviewing a product that has copyright without permission from business actors. This study applies a normative method with a statutory approach. Data collection techniques were carried out by examining existing library materials. The sources of law used are divided into two, namely primary and secondary sources of law which are then analyzed by methods of legal interpretation, legal argumentation, and legal construction. The results of the study reveal that the activity of reviewing a product is also regulated through Article 27 paragraph (3) of Law 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning information and electronic transactions aimed at protecting brands from good name numbers.